Human Rabies: Knowledge and self-reported practices among grade ten school children in a suburban community in Sri Lanka - D. M. S. Jayawardene; N. S. Gunawardena (College of Community Physicians of Sri Lanka, 2015)
Journal of the College of Community Physicians of Sri Lanka 2014; 20(1): 26-36